Decreased proportions of CD4 + IL17+/CD4 + CD25 + CD127− and CD4 + IL17+/CD4 + CD25 + CD127 − FoxP3+ T cells in children with autoimmune thyroid diseases*. (3rd July 2016) - Bossowski, Artur; Moniuszko, Marcin; Idźkowska, Ewelina; Grubczak, Kamil; Singh, Paulina; Bossowska, Anna; Diana, Tanja; Kahaly, George J.
Abstract: Until now, altered balance of Th1 and Th2 immune cells has been postulated to play an important role in the pathogenesis of autoimmune thyroid diseases (AITD). However, recent studies on thyroid diseases have suggested a new role for Th17 cells that have been classified as a new lineage, distinct from Th1, Th2 and Treg cells. Despite wide interest, the role of Th17 cells in the pathogenesis of inflammatory and autoimmune diseases is still debated. The aim of the study was to estimate the proportions of Th17/Treg T cells in peripheral blood from patients with Graves' disease (GD; n = 29, mean age 15.4 ± 5.1 years), Hashimoto's thyroiditis (HT; n = 39, mean age 15.2 ± 4.1 years) and in healthy controls ( n = 49, mean age 14.8 ± 3 years). Polychromatic flow cytometry and several fluorochrome-conjugated monoclonal antibodies were applied to delineate Th17 and Treg cells. The analysis of Th17/Treg T cell proportions in peripheral blood from patients with Graves' disease revealed significantly lower ratios of CD4 + IL17+/CD4 + CD25 + CD127 − ( p < 0.0021) and CD4 + IL17+/CD4 + CD25 + CD127 − FoxP3 + ( p < 0.0031) than in the control group. In addition, in the case of HT, we observed a significant decrease in the ratios of CD4 + IL17+/CD4 + CD25 + CD127 − ( p < 0.0001) and CD4 + IL17+/CD4 + CD25 + CD127 − FoxP3 + ( p < 0.0001) T cells in comparison to healthy children. In patients with untreated GD, a statistically significant positive correlation was found between the proportions of CD4 + IL17+/CD4 + CD25 + CD127−, CD4 + IL17+/CD4 + CD25 + CD127 − FoxP3+ T cells and the TRAbs ( R = 0.71, p < 0.029; R = 0.72, p < 0.026, respectively) and a positive correlation was noted between the percentage of CD4 + CD − IL − 17 + T cells and the level of TSAbs ( R = 0.66, p < 0.037). We conclude that the changes in the proportion of Th17/Treg T cells in peripheral blood and their significant relationship with the level of anti-thyroid antibodies indicate an involvement of these cells in the pathogenesis of AITD.